Conservative Management and Biological Treatment Strategies for Osteochondral Lesions of the Talus: Results from an International Consensus Meeting. Issue 3 (14th September 2018) - ,
Category: Ankle Introduction/Purpose: Cartilage lesions of the talus are a challenging clinical pathology for orthopaedic surgeons. To date, the treatment guidelines for these lesions have been based on both low quality and low levels of evidence. Therefore, an international consensus group of experts was convened to collaboratively advance toward consensus opinions on key topics regarding cartilage lesions of the talus. Conservative management and biological treatment strategies are controversial and were discussed as one portion of the first International Consensus Meeting on Cartilage Repair of the Ankle. The purpose of this abstract is to explain the process and delineate the consensus statements derived from this consensus meeting on conservative management and the use of biological treatment strategies for osteochondral lesions of the talus. Methods: 75 national and international experts in cartilage repair of the ankle, representing 25 countries and all six continents, were convened and participated in a process based on the Delphi method of achieving consensus. Experts were assigned to groups separated by topics, including conservative management and biological treatment strategies. Questions and statements were drafted within the groups and a comprehensive literature review was performed and, where possible, used to confirm or dispute the recommendations made. In addition, the available evidence for each statement was graded. Once the statements achieved majority vote within the working groups, a vote to the overall group was undertaken. The statements were then further edited on the basis of the discussion and votes within the entirety of the consensus group. A final vote then occurred and the strength of consensus was characterized as follows: consensus: 51 - 74%; strong consensus: 75 - 99%; unanimous: 100%. Results: 15 statements addressing conservative management and biological treatment strategies for osteochondral lesions of the talus reached some degree of consensus. In the case of conservative management, 81% (strong consensus) voted in favor of the optimal protocol for an acute non-displaced lesion being immobilization for 4-6 weeks with touchdown weightbearing, with non-steroidal anti-inflammatory drugs only prescribed in cases of significant pain and swelling. With respect to biological strategies, 90% of participants concluded that human cell/tissue products and orthobiologics may improve the quality of repair tissue and improve patient outcomes. However, there is currently no optimal formulation, cell source, or cell concentration of the available biological products in the setting of cartilage repair. Conclusion: There is a lack of evidence-based guidelines available to direct treatment for clinicians when managing osteochondral lesions of the ankle. This international consensus derived from leaders in the field will assist clinicians with a combination of expert- and evidence-based guidelines to consider in the treatment of a cartilage lesion of the talus using conservative management or biological treatment strategies.